Risk Identification and Mitigation Processes for Using Scrum in Global Software Development: A Conceptual Framework - Hossain, E.; Babar, M.A.; Hye-young Paik; Verner, J. (2009 16th Asia-Pacific Software Engineering Conference, 2009)
There is growing interest in applying agile practices in Global Software Development (GSD) projects. But project stakeholder distribution in GSD creates a number of challenges that make it difficult to use some agile practices. Moreover, little is known about what the key challenges or risks are, and how GSD project mangers deal with these risks while using agile practices. We conduct a Systematic Literature Review (SLR) following existing guidelines to identify primary papers that discuss the use of Scrum practices in GSD projects. We identify key challenges, due to global project distribution, that restrict the use of Scrum and explore the strategies used by project managers to deal with these challenges. Our findings are consolidated into a conceptual framework and we discuss various elements of this framework. This research is relevant to project managers who are seeking ways to use Scrum in their globally distributed projects.